The Influence of Creativity and Innovation on Business Performance (Studies on Online Business Actors in Makassar) - Indra Rukmala Nur; Inanna Inanna; Muhammad Rakib; Muhammad Hasan; Rahmatullah Rahmatullah (HUMAN: South Asian Journal of Social Studies, 2021)
. This study aims to describe the creativity, innovation and performance of online businesses in Makassar and the influence of creativity and innovation on business performance (a study of online business people in Makassar). This research uses a quantitative approach and a type of correlational research. The data collection technique is done by observing, documenting and distributing questionnaires (questionnaires). The population in this study is an unknown number of online business people in the city of Makassar and the number of samples needed in this study is as many as 64 people who are considered to be able to describe or answer the aims and problems of the researcher. The analysis technique used is multiple linear regression. The results showed that online business people in the city of Makassar had a level of creativity, innovation and business performance dominated by the medium category. Partially, the creativity variable has a positive effect on business performance, and the innovation variable has a positive effect on the business performance of online business people in Makassar, while simultaneously the creativity and innovation variables have a positive and significant effect on the business performance of online business people in the city of Makassar